Obraz życia wspólnotowego w dobie średniopolskiej na podstawie górnośląskich ksiąg sądowych - Siuciak, Mirosława (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The article presents excerpts from Polish-language court records made from the sixteenth to the eighteenth century in Upper Silesia. Emerging from these books is an image of life in small communities as seen through the lens of financial transactions, inheritance processes, financial claims within families, cases of disorderly behaviourand violations of social order. The quoted fragments show how the society and the officials representing it managed establishing legal rules for the community and how legal texts were constructed. Although they reflect the schematic manner typical of official regulations, many of the phrases they include allow us to recreate the method used for the construction of the text or even their author’s thought process (writing it or commissioning its writing to a qualified official). These texts provide an opportunity to reconstruct the system of values that served as a basis for the functioning of a given community and the internal hierarchy that guaranteed social order.